2023
DOI: 10.1163/1821889x-bja10046
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Absenteeism and Poor Learning Outcome in Tanzania: Rethinking an Incentive Scheme as a Strategic Solution to the Problem

Abstract: The purpose of this study was to determine the best strategically sound tactical response to teacher absenteeism that would enhance teacher effectiveness and learning outcomes in Tanzania. The study was guided by two theories; self-determination theory (2000) and Maslow’s hierarchy of needs theory (1943). A qualitative case study design was used to obtain the results. The study used a sample size of ten research participants comprising of eight habitually absent teachers and two primary school heads. Interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…A study discovered that the issue of teacher absenteeism and poor learning outcomes can be resolved by providing extrinsic motivation, such as a financial incentive for teachers based on their teaching effort and appreciating the intrinsic motivation at the same time. The study recommends that the government should prioritize teacher motivation as suggested by Maslow's hierarchy of needs theory (Juma and Stonier, 2023). From governments around the world, to leaders like the ones in the Tanzanian orphanage, to parents, and to teachers, everyone has to be involved in a child's educational pursuit for them to flourish.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…A study discovered that the issue of teacher absenteeism and poor learning outcomes can be resolved by providing extrinsic motivation, such as a financial incentive for teachers based on their teaching effort and appreciating the intrinsic motivation at the same time. The study recommends that the government should prioritize teacher motivation as suggested by Maslow's hierarchy of needs theory (Juma and Stonier, 2023). From governments around the world, to leaders like the ones in the Tanzanian orphanage, to parents, and to teachers, everyone has to be involved in a child's educational pursuit for them to flourish.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%